DETERMINAN VOLUME EKSPOR CRUDE PALM OIL (CPO) INDONESIA KE NEGARA - NEGARA TUJUAN UTAMA EKSPOR - Lilis Komala, (2023)
Crude Palm Oil (CPO) is Indonesia's leading agricultural commodity that has a large contribution to Indonesia's non-oil exports. Based on these advantages, Indonesia's CPO export performance should have a positive growth result. In fact, export performance is still fluctuating to the main export destination countries. This study aims to examine the effect of land area, total production, international prices, and exchange rates on Indonesia's CPO export volume to Pakistan and United States. This study uses secondary data in the form of time series for the quarter 2012 - 2021 obtained from the Central Statistics Agency, Directorate General of Agricultural, International Monetary Funds, World Bank, and UPNVJ Digital Lab of Economics. The results of multiple linear regression testing state that (1) land area has a significant effect on the volume of Indonesian CPO exports to Pakistan and has no significant effect on the volume of Indonesian CPO exports to United States (2) total production has a significant effect on the volume of Indonesian CPO exports to Pakistan and has no significant effect on the volume of Indonesian CPO exports to United States, (3) international price has no significant effect on the export volume of Indonesian CPO to Pakistan and United States (4) exchange rate has a significant effect on the export volume of Indonesian CPO to Pakistan and United States.